Analisis Kestabilan Sistem Sulselbar akibat Dinamik Load Menggunakan Metode Operation Rescheduling - Indar Chaerah Gunadin; Zaenab Zaenab; Muhammad Jibral Agung; Anwarriska Apriana; Agus Siswanto (Jurnal Penelitian Enjiniring, 2018)
Load scheduling is essential for optimizing power transmission on the system. The way to produce a stable electrical energy transmission system is to minimize transmission losses using between the moment of inertia and power on the generator. The generation noise is a description of the power losses on the transmission line generated when the power plant sends the load power. Transferring power from a high losses plant to a low losses plant. Rescheduling System can minimize transmission system losses. In this research, the scheduling result of this method is compared with the realization of scheduling of thermal generators from PT PLN (Persero) Sulselbar Central Disbursement and Control Center (P3B). This comparison aims to prove this method better than scheduling realized PLN, so that found also advantages and disadvantages method. After the research, this method produces a generation power that is close to stability, because the amount of power generated close to the power generation of PLN in fulfilling the same load demand remains with smaller transmission losses and cheaper fuel costs. The result of stable loading results in the efficiency of the electricity company so that it can reduce the operational cost of the generation and of course indirectly impact on the low cost of electricity production.